Reproduction and milk production performance of buffaloes under field conditions in Guntur district of Andhra Pradesh - A. ANITHA; B.SUBRAHMANYESWARI, G. CHANDRA SEKHAR REDDY, S. JAGADEESWAR (Indian Journal of Animal Production and Management, 2019)
A study was undertaken in Guntur district of Andhra Pradesh to know the performance of Murrah, graded Murrah and local buffaloes in field conditions. The study revealed that the average age at first calving, service period, calving interval and dry period were significantly (P≤0.01) lower in Murrah than that in graded Murrah and local buffaloes. The mean peak yield, lactation milk yield and lactation length was significantly (P≤0.01) higher in Murrah than that in graded Murrah and local buffaloes in the study area. The average age at first calving (months) of graded Murrah buffaloes was significantly (P≤0.05) lower in commercial milk producers than that in small farmers and landless milk producers in the study area. The average dry period of graded Murrah buffaloes was significantly (P≤0.01) lower in commercial milk producers than that in small farmers and landless milk producers. The average service period and calving interval of graded Murrah buffaloes were significantly (P≤0.01) lower in small farmer category than that in commercial milk producers. The mean peak yield, lactation milk yield and lactation period of graded Murrah buffaloes were significantly (P≤0.01) higher in the commercial milk producers than that in small farmer and landless milk producers.